2009
DOI: 10.1088/0953-2048/22/3/034012
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Pb and Ag doping on theJc(H,T) dependence and the mechanical properties of Bi-2212 textured rods

Abstract: Textured rods of Bi-2212 based materials with nominal compositions Bi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…The size as well as the shape of the grains varies in different cuprate HTSc [18][19][20]. This variation in microstructure in turn leads to different superconducting behavior.…”
Section: Grain Size and Gain Connectivity In Cuprate High Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…The size as well as the shape of the grains varies in different cuprate HTSc [18][19][20]. This variation in microstructure in turn leads to different superconducting behavior.…”
Section: Grain Size and Gain Connectivity In Cuprate High Temperaturementioning
confidence: 99%
“…Also, A. Sotelo et al [20] have studied the Lead (Pb) and Silver (Ag) doping of Bi-2212 samples. It was found that Pb doping results in the decrease of the transport critical current density (see Fig.…”
Section: (Bi Pb) 2 Sr 2 Ca N−1 Cu N Oymentioning
confidence: 99%
“…Since the discovery of high-Tc superconductivity in Bi-based high-temperature superconductors (HTSC) [1], which provides the most promising materials for potential technological and industrial applications [2][3][4], intense studies have been performed [5][6][7][8][9][10][11][12][13][14][15][16][17][18] in order to improve its critical temperature (Tc), critical current density (Jc), and better understand the structural properties of the system. As it is well-known, the Bi-based superconductor family comprises three different phases which can be described by the Bi 2 Sr 2 Ca n-1 Cu n O 2n+4+y general formula, where n =1, 2 and 3.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are related with the preparation of high homogeneous precursors with small particle sizes using different synthetic methods [14][15][16][17] while other ones have been centered on the grain orientation [18][19][20]. Moreover, the effect of cationic substitution on the superconducting properties of these materials has been studied in previous works, as for example Pb 2+ by Bi 3+ [21][22][23], or metallic additions, typically metallic Ag [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%